Denésoliné (Chipewyan) Knowledge of Barren-Ground Caribou (Rangifer tarandus groenlandicus) Movements - Kendrick, A.; Lyver, P.O.'B.; Dene First Nation, Lutsël K'é (ARCTIC, 2010)
Semi-directed interviews relating to the traditional knowledge (TK) of barren-ground caribou (Rangifer tarandus groenlandicus) movements were conducted with elders and hunters from the Denésoliné (Chipewyan) community of Lutsël K’é, Northwest Territories, Canada. The objective was to document Denésôliné knowledge of past and present caribou migration patterns and record their explanations for perceived changes in movements. Elders recognized expected and unusual levels of variation in caribou movements. Local narratives show that Denésoliné communities have a fundamental awareness of caribou migration cycles. Most elders thought fire frequency and intensity had increased over their lifetimes and that caribou numbers and distribution had been affected. The majority of Lutsël K’é elders thought mining development was affecting caribou movements in some way. Elders believe that disturbance around traditional migration corridors and water crossings and disturbance of “vanguard” animals might be forcing caribou to use less optimal routes and influencing where they overwinter. Elders also believe that a lack of respect for caribou will cause the animals to deviate from their “traditional” migration routes and become unavailable to the people for a period of time. Wildlife management practices may need to further accommodate aboriginal perspectives in the future. Des entrevues semi-dirigées relatives au savoir traditionnel (ST) sur les déplacements du caribou des toundras (Rangifer tarandus groenlandicus) ont été faites auprès d’aînés et de chasseurs de la communauté denésoliné (chippewyan) de Lutsël K’é, dans les Territoires du Nord-Ouest au Canada. L’objectif était de documenter le savoir denésôliné concernant les habitudes migratoires passées et présentes du caribou, et de consigner les explications sur les changements perçus dans les déplacements. Les aînés ont reconnu des niveaux de variation anticipés et inusités dans la migration du caribou. Des récits locaux révèlent que les communautés denésoliné possèdent ...